2020
DOI: 10.1002/app.49872
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of composite anion exchange membranes based on in‐situ copolymerization of N‐vinyl formamide and divinylbenzene in porous PTFE

Abstract: A series of composite anion exchange membranes was synthesized via in-situ copolymerization of various ratios N-vinyl formamide (NVF) and divinylbenzene (DVB), supported by porous polytetrafluoroethylene (PTFE) polymer matrix, and followed by alkaline hydrolysis, and quaternization of the composite membranes with epoxypropyltrimethylammonium chloride (EPTMAC). FTIR and SEM analyses revealed that the composite membranes were successfully prepared. Moreover, the hydrophilic property of the composite membrane imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…DVB and TMHDA were selected for this study as they are commercially available reagents that can be purchased in bulk quantities and have been used to crosslink a wide variety of IEMs. 11,16,20,21 As can be seen with the data presented in the ESI † involving ETFE-based RG-AEMs made with a selection of commercially available diamines, TMHDA showed the most promise (on a permselectivity evaluation basis).…”
Section: Aim and Scope Of The Studymentioning
confidence: 71%
“…DVB and TMHDA were selected for this study as they are commercially available reagents that can be purchased in bulk quantities and have been used to crosslink a wide variety of IEMs. 11,16,20,21 As can be seen with the data presented in the ESI † involving ETFE-based RG-AEMs made with a selection of commercially available diamines, TMHDA showed the most promise (on a permselectivity evaluation basis).…”
Section: Aim and Scope Of The Studymentioning
confidence: 71%
“…In this paper, we investigated the antiproliferative and oxidative effects of HEMA based cryogels containing different amounts of N-Vinylformamide (NVF) as comonomer on Saccharomyces cerevisiae BY4741 cells, which were previously synthesized and characterized [5]. NVF is a hydrophilic monomer which has stronger reactivity and much lower toxicity than acrylamide [17]. Previously, we have shown that these cryogels are promising candidates for potential articular cartilage biomaterials [18].…”
Section: Introductionmentioning
confidence: 99%